2004
DOI: 10.1109/tpwrd.2004.829139
|View full text |Cite
|
Sign up to set email alerts
|

Electrical Parameters Associated With Discharges in Resistive Soils

Abstract: The electrical parameters associated with discharges in resistive soils have been studied under inhomogeneous fields in order to achieve a better understanding of the nonlinear behavior of grounding systems subject to high surge currents. The soil resistivity and the other parameters associated with discharges are defined using experimental and calculating methods. The dielectric strength is found to be a function of water content of the soil. The same goes for the discharge-guiding field. The inception curren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0

Year Published

2009
2009
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(10 citation statements)
references
References 12 publications
0
10
0
Order By: Relevance
“…where, Ec is in kVm -1 and ρ is in m Ω ⋅ [4]. In addition, it is shown that the residual soil resistivity in the ionization region is approximately 7% of the original soil resistivity based on the several experimental results [5], which is applied in the paper to model the performance of grounding system including the non-linear soil ionization phenomenon.…”
Section: Consideration Of Soil Ionizationmentioning
confidence: 99%
“…where, Ec is in kVm -1 and ρ is in m Ω ⋅ [4]. In addition, it is shown that the residual soil resistivity in the ionization region is approximately 7% of the original soil resistivity based on the several experimental results [5], which is applied in the paper to model the performance of grounding system including the non-linear soil ionization phenomenon.…”
Section: Consideration Of Soil Ionizationmentioning
confidence: 99%
“…Also soil discharges are a critical factor to change in the transient performance of grounding systems, i.e., they may reduce the impulse impedance of grounding systems. Thus far, many researchers have realized extensive experiments in order to establish a model capable of describing the dynamic behavior of grounding electrode systems at high impulse voltages [2][3][4][5]. From many experimental and simulation results, it was concluded that the dynamic behavior of grounding systems at high impulse currents depends not only on the characteristics of soil ionization but also on the discharge mechanisms [6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%
“…To evaluate the performance of a grounding system subjected to current impulses, there is no consensus among authors about which quantities should be considered [6,7].…”
Section: Introductionmentioning
confidence: 99%
“…From studies where the composition and soil moisture were controlled in the laboratory [7], it was concluded that the ionization of the soil is a very important phenomenon in discharge process because, under high current impulses, it reduces the soil resistance.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation